Oral clefts, consanguinity, parental tobacco and alcohol use: a case-control study in Rio de Janeiro, Brazil - Isabel Cristina Gonçalves Leite; Sérgio Koifman (Sociedade Brasileira de Pesquisa Odontológica, 2009)
This hospital-based, case-control study investigated the possible associations between family history of malformations, parental consanguinity, smoking and alcohol drinking and nonsyndromic orofacial cleft (OC, subdivided in 2 main groups: CL/P - cleft lip with or without cleft palate and CP - cleft palate alone). 274 cases were matched (age, sex and place of residence) to 548 controls. Odds ratios (OR) and 95% confidence intervals (95% CI) - adjusted for maternal age, schooling and smoking / alcohol use - were calculated by conditional logistic regression. The results demonstrated that the history of oral clefts either in the father's (CL/P: OR = 16.00, 5.64-69.23; CP: OR = 6.64, 1.48-33.75) or in the mother's family (CL/P: OR = 5.00, 2.31-10.99, CP: OR = 12.44, 1.33-294.87) was strongly associated with both types of clefts, but parental consanguinity was associated only with CL/P (OR = 3.8, 1.27-12.18). Prevalence of maternal smoking during the first trimester of pregnancy was higher among cases but the OR (1.13, 0.81-1.57) was not statistically significant. Maternal passive smoking (nonsmoking mothers) during pregnancy was associated with CL/P (1.39, 1.01-1.98) but not with CP. Maternal alcohol use during the 1st trimester increased odds for CL/P (OR = 2.08, 1.27-3.41) and CP (OR = 2.89, 1.25-8.30), and odds for OC tended to increase with dose. Neither smoking nor alcohol use by fathers increased risks for OC. This study provides further evidence of a possible role of maternal exposure to tobacco smoke and alcohol in the etiology of nonsyndromic oral clefts.